Obesity and Heredity for Diabetes Mellitus among Elderly - Setyawati, Asih Dewi; Ngo, Thi hai Ly; Padila, Padila; Andri, Juli (JOSING: Journal of Nursing and Health, 2020)
The study has a purpose to determine obesity and heredity in diabetes mellitus case among elderly in Bengkulu. The method in this study was descriptive correlation design with the total samples were 42 elderly in Primary Health Center calls Sukamerindu, Bengkulu. The data has collected from January until March 2019. The results of unvaried study shows there were 21 people (50%) of elderly who are obese, 21 people (50%) of respondents with heredity,14 people (33.3%) with diabetes mellitus. According to the results of chi-square test, it found there was a significant correlation with obesity and genetic factor for diabetic mellitus among elderly in Bengkulu with p-value 0.003 and OR 12.667. In summary, obesity and genetic factors can increase the case of diabetes mellitus among elderly in Primary Health Center, Bengkulu. By giving an enough education and counseling by expert that will reduce the incidence of diabetes mellitus among in Primary health Center Sukamerindu, Bengkulu. Keywords: Diabetes Mellitus, Heredity, Obesity